A tenderfoot in Colorado - Townshend, R. B., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2008)
Now back in print, A Tenderfoot in Colorado is R.B. Townshend's classic account of his time in the wild frontier territory known as Colorado. Townshend arrived in the Rockies in 1869, fresh from Cambridge, England, with 300 in his pockets. He found friends among some of Colorado's more colorful characters, people who taught him much about life on the frontier. Jake Chisolm taught him how to shoot after rescuing him from two men preparing to skin him at poker. Wild Bill of Colorado taught him the meaning of "the drop" and warned him against wearing a gun in town unless he wanted trouble.
Keywords: Pioneers -- Colorado -- Biography; English -- Colorado -- Biography; Frontier and pioneer life -- Colorado; Colorado -- Description and travel; Rocky Mountains -- Description and travel; Colorado -- History -- To 1876; Townshend, R. B. (Richard Baxter), 1846-1923 -- Travel -- Colorado